2008
DOI: 10.1158/1078-0432.ccr-07-4744
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Natural Killer Cell-Mediated Antitumor Effects of Low-Dose Bortezomib in Hepatocellular Carcinoma

Abstract: Purpose: Hepatocellular carcinoma (HCC) displays particular resistance to conventional cytostatic agents. Alternative treatment strategies focus on novel substances exhibiting antineoplastic and/or immunomodulatory activity enhancing for example natural killer (NK) cell antitumor reactivity. However, tumor-associated ligands engaging activating NK cell receptors are largely unknown. Exceptions are NKG2D ligands (NKG2DL) of the MHC class I-related chain and UL16-binding protein families, which potently stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 37 publications
2
58
1
Order By: Relevance
“…Lundqvist et al [6 ]also demonstrated that bortezomib could sensitize murine tumor cells to perforin/granzyme as well as tumor necrosis factor-related apoptosis-inducing ligand-mediated apoptosis. Another recent study demonstrated that bortezomib can downregulate MHC class I molecules and enhance the sensitivity of myeloma to NK cell-mediated lysis [8], and that bortezomib can also promote upregulation of NKG2D, thereby enhancing NK cell cytotoxicity [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Lundqvist et al [6 ]also demonstrated that bortezomib could sensitize murine tumor cells to perforin/granzyme as well as tumor necrosis factor-related apoptosis-inducing ligand-mediated apoptosis. Another recent study demonstrated that bortezomib can downregulate MHC class I molecules and enhance the sensitivity of myeloma to NK cell-mediated lysis [8], and that bortezomib can also promote upregulation of NKG2D, thereby enhancing NK cell cytotoxicity [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…34 Sodium butyrate, a potent repressor of histone deacetylase (HDAC), could upregulate expression of NKG2D ligand MICA/MICB in HeLa and HepG2 cell lines and increase their susceptibility to NK lysis. 35 Low-dose Bortezomib mediated a specific dual antitumor effect in hepatocellular carcinoma by inhibiting tumor cell proliferation and increasing MICA/B protein expression levels on the surface of hepatoma cells, thus stimulating cytotoxicity of cocultured NK cells, 36 similarly to our findings that RES could improve CIKs-mediated cytolysis by upregulating the cell-surface expression of NKG2D ligands ULBP1-3 in KG-1a cells because after expressions of cell-surface ULBP1-3 were all blocked, cytolysis of CIKs against KG-1a/RES cells decreased. Additionally, our data showed that RES could significantly upregulate the mRNA of MICA/MICB and ULBP1-3 in the KG-1a cells, different from the protein distributions on cell surface.…”
Section: Methodsmentioning
confidence: 99%
“…20). Bortezomib was also shown to differentially affect the expression of E2F1, p21, and p27 (21) and to mediate a specific dual antitumor effect via natural killer (NK) cell antitumor reactivity (22). An international, multicenter phase II trial (23) and several preclinical studies (24)(25)(26) of bortezomib in HCC patients have been reported.…”
Section: Introductionmentioning
confidence: 99%